2022
DOI: 10.3390/ijms23042154
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Binding Protein 6 Inhibition Decreases Cell Cycle Progression, Migration and Autophagy in Bladder Cancers

Abstract: Bladder cancer (BC) has a high recurrence rate worldwide. The aim of this study was to evaluate the role of fatty acid binding protein 6 (FABP6) in proliferation and migration in human bladder cancer cells. Cell growth was confirmed by MTT and colony formation assay. Western blotting was used to explore protein expressions. Wound healing and Transwell assays were performed to evaluate the migration ability. A xenograft animal model with subcutaneous implantation of BC cells was generated to confirm the tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…FABP6 is a BA transporter in ileal epithelial cells and is critical for the enterohepatic circulation of BAs 25 . FABP6 also participates in the progression of numerous types of cancer [26][27][28] . Compared with adjacent normal liver tissues, overexpressed FABP6 was observed in HCC tissues 29 .…”
Section: Discussionmentioning
confidence: 99%
“…FABP6 is a BA transporter in ileal epithelial cells and is critical for the enterohepatic circulation of BAs 25 . FABP6 also participates in the progression of numerous types of cancer [26][27][28] . Compared with adjacent normal liver tissues, overexpressed FABP6 was observed in HCC tissues 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al showed that fatty acid binding protein 6 (FABP6) regulates cell cycle progression and autophagy in bladder cancer (BC) cells [3]. Knockdown of FABP6 inhibited BC cell growth via regulation of cell-cycle-related protein expressions.…”
mentioning
confidence: 99%
“…PDGFRA and PDGFRB exert a central function in the initiation and progression of many tumors, including glioblastoma, gastrointestinal stromal tumor, skin squamous cell carcinoma, and oral squamous cell carcinoma [ 40 , 41 , 42 , 43 ]. FABP6 has been reported as a potential target for inhibiting the progression of BLCA, and the mechanism may involve several aspects, such as affecting the activation of the AKT-mTOR signal and cell cycle [ 44 ]. NRP2 exerts a key role in lymphangiogenesis and lymphovascular invasion and affects the function of epithelial–mesenchymal transformation in the evolution of tumor transmission and metastasis [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%